Faithful Learning and the Christian Scholarly Vocation (Teaching theology and religion, 2006)
Books reviewed: Henry, Douglas V. and Agee, Bob R., eds., Faithful Learning and the Christian Scholarly Vocation Reviewed by Laura K. Simmons George Fox Evangelical Seminary